Las tics y su incidencia en el aprendizaje de la asignatura de base de datos, del primer año de bachillerato general unificado de la Unidad Educativa Ciudad de Valencia, cantón Valencia, año 2017 - Vinces Olmedo, Manuel Benito (2017)
The Educational Unit "Ciudad de Valencia" has gained merit because it is a prestigious institution that uses technological and innovative methods for the academic development of students, in order that they perform in each subject in the best way. Currently, every Educational Institution must analyze and study effective learning processes to provide students with the ease and interest to acquire knowledge of certain subjects from which they become complex. That is why we take into consideration a study on the use of tics and its impact on learning the subject of Database for the First Baccalaureate of the Institution, which will focus on a profound change in the way in which the students communicate and interact in the educational field for the learning of the subject Database